Development of a Character Education-Based Mathematics E-Comic to Improve Elementary School Students’ Numeracy Literacy Skills - Buchari Buchari; Wiendi Wiranty; Dwi Oktaviana; Utin Desy Susiaty (JPMI (Jurnal Pendidikan Matematika Indonesia), 2026)
Numeracy literacy in Indonesia requires attention, as it remains low, as revealed in the Program for International Student Assessment (PISA) report. A mathematics learning process that can support mathematical abilities, particularly mathematical literacy, must be supported by the characteristics of media skills or tolls that can be adapted to the learning environment. This study aims to develop a mathematics e-comic based on character education to improve elementary school students’ numeracy literacy skills. The research employed a Research and Development (R&D) approach using a simplified Borg & Gall model consisting of seven stages: (1) identifying potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product trial, and (7) final product revision. The participants were 27 fifth-grade students of SD Negeri 55 Pontianak Barat. Research instruments included expert validation sheets, numeracy literacy tests, and student response questionnaires. The validation results indicated that the e-comic was highly feasible, with scores of 90.67% (content expert) and 93.33% (media expert). The trial results revealed significant improvement in students’ numeracy literacy. The average score for identifying relevant information increased from 64.20 to 92.59, applying whole number operations in real-life problems improved from 62.96 to 93.83, and presenting problem-solving processes with logical reasoning rose from 46.30 to 74.07. The overall average increased from 57.82 to 86.83, reflecting a 50.19% improvement. These findings proves that character education-based e-comic are effective in improving students’ numeracy literacy skills.Rancang Bangun E-Comic Matematika Berbasis Pendidikan Karakter Dalam Meningkatkan Kemampuan Literasi Numerasi Siswa di Sekolah DasarABSTRAKLiterasi numerasi di Indonesia perlu diperhatikan, karena masih rendah seperti yang diungkapkan dalam laporan Program for International Student Assessment (PISA). Proses pembelajaran matematika yang dapat menunjang kemampuan matematika terutama kemampuan literasi matematika tentunya harus didukung dengan karakteristik keterampilan media atau sarana yang dapat disesuaikan dengan kondisi lingkungan belajar. Penelitian ini bertujuan untuk mengembangkan e-comic matematika berbasis pendidikan karakter dalam meningkatkan kemampuan literasi numerasi siswa sekolah dasar. Model pengembangan yang digunakan adalah Borg & Gall yang disederhanakan menjadi tujuh tahap: (1) potensi dan masalah, (2) pengumpulan data, (3) desain produk, (4) validasi desain, (5) revisi desain, (6) uji coba produk, dan (7) revisi produk. Subjek penelitian adalah 27 siswa kelas V SD Negeri 55 Pontianak Barat. Instrumen penelitian terdiri atas lembar validasi ahli, tes literasi numerasi, dan angket respon siswa. Hasil validasi menunjukkan bahwa produk e-comic layak digunakan dengan skor rata-rata 90,67% (ahli materi) dan 93,33% (ahli media). Hasil uji coba terbatas menunjukkan adanya peningkatan signifikan pada kemampuan literasi numerasi siswa, ditunjukkan dengan skor rata-rata: indikator mengidentifikasi informasi relevan meningkat dari 64,20 menjadi 92,59, indikator menggunakan operasi hitung bilangan cacah meningkat dari 62,96 menjadi 93,83, dan indikator menyajikan proses penyelesaian dengan alasan logis meningkat dari 46,30 menjadi 74,07. Rata-rata keseluruhan meningkat dari 57,82 menjadi 86,83 (peningkatan 50,19%). Temuan ini membuktikan bahwa e-comic berbasis pendidikan karakter efektif meningkatkan kemampuan literasi numerasi siswa.Kata Kunci :e-comic; literasi numerasi; pendidikan karakter; sekolah dasar